Techniques for DiffServ - based QoS in Hierarchically Federated MAN Networks - the GRNET Case - Christos Bouras; Dimitris Primpas; A Liakopoulos; A Varvitsiotis; V Siris; G Fotiadis (The 14th IEEE Workshop on Local and Metropolitan Area Networks (LANMAN 2005), Chania. Island of Crete, Greece, 2005)
DiffServ is the basis of contemporary QoS-enabled networks. Setting up DiffServ QoS requires extensive engineering effort in dimensioning and provisioning, especially for adjacent networks under different administrations linked in a “federated” hierarchy. In this paper we present a case study for QoS techniques employed in the GRNET MAN networks of Athens and Crete. After introducing the supported QoS mechanisms and service types, we discuss our dimensioning methodology and present two algorithms for worst-case dimensioning. We explain the provisioning mechanisms of GRNET and we present in brief our new automated provisioning ANS tool. Finally, we deal with the extension of our mechanisms and tools in hierarchically federated networks and give some future directions of our work.